Ion-pair and anion recognition by macrocycles and interpenetrative assemblies - Picot, S (2013)
This thesis investigates the design and synthesis of macrocycles and examines their ion-pair recognition, anion recognition and interpenetrative assembly capabilities. Chapter One introduces the field of supramolecular chemistry. Key concepts in host–guest complexation and self-assembly are outlined, with particular emphasis on the design of host systems for anion and ion-pair recognition. Chapter Two details the synthesis and binding properties of a heteroditopic 1,2,3-triazole- containing macrocycle that exhibits cooperative ion-pair recognition. Solution and solid-state evidence shows that the triazole motif simultaneously binds anions and cations. The exten- sion of this work towards the formation of interlocked structures containing an expanded heteroditopic macrocycle and threading components is explored. Chapter Three discusses the design and syntheses of series of electron-deficient macrocycles based on imidazolium, pyridinium and triazole. These are investigated for anion binding ability and assembly of interpenetrative assemblies with electron-rich threading components. Chapter Four describes research into the formation of interpenetrative assemblies using neutral components. Their design is based around aromatic donor–acceptor interactions and halogen bonding. Chapter Five presents some conclusions from the research undertaken. Chapter Six provides titration protocols, Job plot approximations, experimental procedures and characterisation of the compounds described in this thesis. Appendix details additional X-ray crystallographic data.